Hello, Hello Brazil : Popular Music in the Making of Modern Brazil - McCann, Bryan, 1968- (Book collections on Project MUSE., 2004)
Hello, hello Brazil" was the standard greeting Brazilian radio announcers of the 1930s used to welcome their audience into an expanding cultural marketplace. New genres like samba and repackaged older ones like choro served as the currency in this marketplace, minted in the capital in Rio de Janeiro and circulated nationally by the burgeoning recording and broadcasting industries. Bryan McCann chronicles the flourishing of Brazilian popular music between the 1920s and the 1950s. Through analysis of the competing projects of composers, producers, bureaucrats, and fans, he shows that Brazilians alternately envisioned popular music as the foundation of a unified national culture and used it as a tool to probe divisions of race and region. McCann explores the links between the growth of the cultural industry, rapid industrialization, and the rise and fall of Getúlio Vargas's Estado Novo dictatorship. He argues that these processes opened a window of opportunity for the creation of enduring cultural patterns and demonstrates that the understandings of popular music cemented in the mid-twentieth century continue to structure Brazilian cultural life in the early twenty-first.